Ethical Identity as a Task of Education. In Search of Modern Tools of Pedagogical Discourse - Boużyk, Maria Małgorzata (Forum pedagogiczne, 2019)
The article presents a philosophical analysis of the ethical identity of man as an exercise for today’s education. It consists of four parts. The first part focuses on the definition of ethical identity and its comparison with cultural identities. The other parts deal with the problem of cultural identities as a bearer of values, relevant to the consumer culture, such as change, visibility and predictability. Discussing these three values in the context of human moral actions allows a formulation of a conclusion about the need to focus education on ethical identity and to support these activities with humanistic education (in the field of philosophy, in particular). Furthermore, the article justifies that the very term “ethical identity”, if interpreted on the basis of classical metaphysics, can be an effective tool for pedagogical discourse. Therefore, attention is paid to the following key philosophical concepts: substantial unity of human being, man as the subject of human acts and freedom as a moral force.